MENURUNKAN CACAT SHRINK PLASTIK PADA PRODUK BOTOL BEDAK MENGGUNAKAN METODE SIX SIGMA - Noviyanti, Aisah; Khamaludin, Khamaludin; Firdaus, M.Yus (Universitas Putera Batam, 2023)
PT XYZ is an industrial sector that produces cosmetic or body care products. By always trying to convince consumers with good product quality. With this, the company always strives to optimize and manage its products and human resources. The problems that occur in this company are caused by poor quality of shrinkage so the company tries to reduce defects resulting from this process. Quality control is a step in controlling a problem with a product so that it can produce good quality in accordance with customer expectations. Six Sigma is a method for controlling a problem in a structured manner. DMAIC (Define, Measure, Analyze, Improve, Control) is a measure in carrying out the Six Sigma process. The results of the research prove that when applied this method can reduce the impact of defects in the product process and is useful for the company to increase profits and as an experience so that if the problem occurs again the company can know how to overcome it.